2023
DOI: 10.1111/nicc.12888
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of increased nursing workload in the COVID‐era: A retrospective analysis of prospectively collected data

Abstract: BackgroundCOVID‐19 is associated with increased nursing workload, therefore a high nurse‐to‐patient ratio would be required.AimTo analyse difference in nursing workload, as expressed with the Nursing Activities Score (NAS), between COVID‐19 patients versus control patients without COVID‐19 disease (NCOVID‐19 group) in an Italian Extracorporeal Membrane Oxygenation (ECMO) centre.Study DesignRetrospective analysis of prospectively collected data, enrolling consecutive patients admitted to a general Intensive Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…While these studies all showed a reduction of these three aspects, it remains uncertain if this truly reflects a reduction in ICU staff workload, during different phases of mechanical ventilation: for example, the weaning phase in particular, is seen as a labour-intensive phase of mechanical ventilation 64 . We need better studies in the future that, for instance, capture nursing activities scores with metrics that encompass the majority of tasks of an ICU nurse, including those related to invasive ventilation 65,66 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these studies all showed a reduction of these three aspects, it remains uncertain if this truly reflects a reduction in ICU staff workload, during different phases of mechanical ventilation: for example, the weaning phase in particular, is seen as a labour-intensive phase of mechanical ventilation 64 . We need better studies in the future that, for instance, capture nursing activities scores with metrics that encompass the majority of tasks of an ICU nurse, including those related to invasive ventilation 65,66 …”
Section: Discussionmentioning
confidence: 99%
“…64 We need better studies in the future that, for instance, capture nursing activities scores with metrics that encompass the majority of tasks of an ICU nurse, including those related to invasive ventilation. 65,66 Closed loop ventilation can facilitate rapid and precise adjustments to ventilator settings. In ICU subpopulations, such as traumatic brain injury patients, strict and precise titration of paCO 2 and paO 2 values are fundamental in order to optimise intracerebral physiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing administrative responsibilities, broadening interprofessional communication, the introduction of integrative medicine such as hypnosis, and the inclusion of patients' family in their care undeniably contribute to modifications in the determinants of nursing workload in the ICU. 19 Hence, conducting a prospective evaluation that matches subjective perceptions with objective measures rather than solely relying on activity-or timebased assessments is essential for achieving a more reliable workload evaluation. Enhanced reliability in workload measurement is important for various aspects of nursing practice and health care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…As the number of our submissions and accepted papers has increased, so too must the number of papers published in our issues, with this issue featuring around 25 papers around a number of themes, such as sleep promotion, 1,2 the impact of COVID-19 on both patients' experiences and nurses, [3][4][5][6][7][8][9] technology use in the intensive care unit (ICU) 10,11 and quantitative research, involving statistics. 1,2,[12][13][14] Our statistical advisor Dr. Chao Huang, in collaboration with the editors, has written an informative guest editorial 15 around why it is so important that nurses can understand basic statistics to be able to read and interpret papers such as these. Many of the papers in this issue are primarily quantitative in nature and use some form of statistical analysis in their results.…”
Section: Introduction To the Issue And Goodbye As Co-editor In Chiefmentioning
confidence: 99%